Physiological measurements of tissue health; implications for clinical practice - Kim, Jennifer H (Int Wound J, 2012)
Pressure mapping alone insufficiently describes tissue health. Comprehensive, quantitative non invasive assessment is crucial. Interface pressures (IPs) and transcutaneous blood gas levels [transcutaneous tissue oxygen (T(c)PO(2))] were simultaneously assessed over both ischia and the sacrum to investigate the hypotheses: (i) tissue oxygenation decreases with sustained applied pressure; (ii) tissue oxygen and IP are inversely correlated in loaded soft tissues; (iii) multisite assessments are unnecessary because healthy individuals are symmetrical. Measurements were taken at 5‐minute intervals for 20 minutes in both sitting and supine lying for a cohort of 20 able‐bodied adults. There were no statistically significant changes over time for either variable in 96% of timepoint comparisons. Specifically, no significant differences were seen between 10 and 20 minutes in either position. These findings imply that a 10‐minute assessment can reliably indicate tissue health and that tissue may adapt to applied load over time. No statistically significant correlations between T(c)PO(2) and IP were observed. However, the left and right ischia were significantly different for both variables in supine lying (P < 0·001) and for sitting IP (P < 0·010). Thus, even in this healthy cohort, postural symmetry was not observed and should not be assumed for other populations with restricted mobility. If a multisite technique cannot be used, repeated tissue health assessments must use the same anatomic location.